Unclassifiable interstitial lung disease and autoimmunity: Towards IPAF in children? - Aoust, Laura; Berteloot, Laureline; Drabent, Philippe; Garcelon, Nicolas; Bodemer, Christine; Molina, Thierry Jo; Bader‐Meunier, Brigitte; Hadchouel, Alice (Pediatric pulmonology, 2023)
Introduction Interstitial pneumonia with autoimmune features (IPAF) has been defined for adults with interstitial lung disease (ILD) and autoimmunity who do not meet the criteria for a specific connective tissue disease (CTD). We aimed to determine whether IPAF criteria could apply to children. Methods We retrospectively studied patients with ILD and autoimmunity followed at Necker Hospital between 2008 and 2019. Children were classified according to specific CTD and IPAF criteria. The epidemiology and course of the disease were studied according to the final diagnosis. Results Among 27 patients, 6 fulfilled the criteria for IPAF and represented 4.5% of all patients with ILD during the study period. Other diagnoses included juvenile dermatomyositis (30%), overlap syndromes (19%), systemic lupus erythematosus (15%), systemic sclerosis (7%), mixed CTD (4%), and rheumatoid arthritis (4%). IPAF patients were more frequently boys versus CTD‐ILD patients (67% vs. 14%, p = .02). Two patients had severe respiratory distress that led to death for one of them. The course was favorable for the others, with a good response to steroids. The course tended to be more favorable for IPAF patients than for those with CTD‐ILD (0% lung fibrosis in the IPAF group vs. 43% in the CTD‐ILD group, p = .07). Conclusion We confirmed the existence of IPAF in children. Its prevalence was lower than in adults but comparable to that found for other pediatric series. Boys were more highly represented than in CTD‐ILD. The course was favorable for most cases. Larger and more prospective studies are needed to confirm these results.